Virtual reality-based sensory stimulation preferences at Amundsen-Scott South Pole station in Antarctica - Stijn J. J. Thoolen; John-Michael Watson; Abigail M. Fellows; Pooja P. Bovard; Gary E. Strangman; Jay C. Buckey; Aleksandra S. Stankovic (npj Microgravity)
Abstract Virtual Reality (VR)-based sensory stimulation can provide relaxation and psychological restoration in isolated, confined and extreme conditions such as long-duration spaceflight, but it remains unclear which aspects of VR would be most beneficial. To investigate individual preferences for various VR attributes, 25 overwintering crew members at the Amundsen-Scott South Pole Station in Antarctica underwent 16 variations of VR stimulation at the end of their mission, with manipulations in delivery mode (VR vs. laptop), content (nature vs. city environments), duration (4 vs. 10 min), and sensory augmentation (with or without temperature cues). Data collection included pre- and post-intervention surveys on perceived quality (value, immersiveness, restorativeness) and mood, as well open-ended qualitative feedback. We found that VR was viable and restorative in a high-fidelity spaceflight analog. Although longer-lasting nature scenes were preferred overall, interindividual variation in preferences for sensory stimulation emphasizes the need for a personalized approach.